An analysis of debt beta and equity beta for publicly and non-publicly traded food and agriculture companies - Travis, Riley (Kansas State University, 2024)
Is there a difference in risk between public and private companies that borrow funds using bonds? The purpose of this thesis is to determine differences in the market risk of companies that are both public and private. Food and agricultural firms are selected for analysis and are viewed using a four-year observation for five-year time intervals on a weekly and monthly basis. The relative risk of these companies is determined in three different ways. The first two ways are by analyzing company bond price changes with the S&P 500 or thirty-year treasury bond prices to determine the debt beta and beta, respectively. The third way is by using the equity beta that is determined with this same set of companies by using the publicly traded, adjusted close prices from Yahoo Finance for each company and the S&P 500. It was found that the debt beta and beta were relatively low, at or close to zero, showing little systematic risk. This means when looking at companies from a bond borrowing standpoint, much of the risk will be unsystematic risk from the company itself. When analyzing the equity beta, the three publicly traded companies track close to one another. There is more systematic risk with the equity beta with it being relatively close to one for each company, meaning these companies are more likely to move with the market. This study shows that there is a stronger relationship with the equity yield to the market than the debt yield. Both the slope (beta) and R-squared are higher when comparing the monthly bond rate to the 30-year treasury than to the S&P 500. Over time, the volatility of the debt and equity betas remain relatively unchanged, with the exception of early COVID-19 influence.
Keywords: Debt beta; Equity beta; Non-public company; Bond risk; Market risk